2009
DOI: 10.1111/j.1440-1827.2009.02458.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of gene methylation in neoplastic and non‐neoplastic gastric epithelia using methylation‐specific DNA microarray

Abstract: A fiber-type DNA microarray was used to calculate methylation rates (MR) of four tumor suppressor genes, lysyl oxidase (LOX), p16, RUNX3, and tazarotene-induced gene 1 (TIG1). MR were calculated in 26 primary gastric cancers and corresponding non-neoplastic gastric epithelia, and the results were compared to those of conventional methylation-specific polymerase chain reaction (MSP). MR ranged from 0.1% to 69.1% (mean, 18.3%) for LOX, 0.5-74.1% (mean, 15.7%) for p16, 0.2-76.5% (mean, 22.7%) for RUNX3, and 0.6-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…As shown in Figure 6A, both mRNA and protein levels of RARRES1 increased drastically at 12 hours and peaked at 24 hours after the addition of doxycycline (Figure 6A). In concurrence with previous reports examining various human cancers [2][4], [6][8], [27], we observed that re-expression of RARRES1 not only augmented cell death induced by cytotoxic agents Paclitaxel and Doxorubicin (Figure 6B), but also impeded cell invasion (upper panel of Figure 6C). …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As shown in Figure 6A, both mRNA and protein levels of RARRES1 increased drastically at 12 hours and peaked at 24 hours after the addition of doxycycline (Figure 6A). In concurrence with previous reports examining various human cancers [2][4], [6][8], [27], we observed that re-expression of RARRES1 not only augmented cell death induced by cytotoxic agents Paclitaxel and Doxorubicin (Figure 6B), but also impeded cell invasion (upper panel of Figure 6C). …”
Section: Resultssupporting
confidence: 92%
“…For the first time, our preceding report [9], as well as current study, depicted a likelihood that tumor suppressor locus, RARRES1 , was progressively methylated prior to undergoing epigenetic silencing. Subsequently, downregulated RARRES1 triggered various malignant properties and was associated with advanced neoplastic states in various cancer types [2][4], [6][8], [27] and in breast carcinomas (current report).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results showed that the degree of methylation in the Acc samples was significantly higher than that in the nsgs, which is consistent with data from several previous studies (48)(49)(50). these results suggest that rUnX3 promoter methylation plays an important role in the genesis and development of Acc.…”
Section: Discussionsupporting
confidence: 82%
“…Another more recent MSP study on 123 GC and 111 healthy patients also reported that 55% of the GC cases showed RUNX3 hypermethylation [77]. Yet, MSP is not a quantitative technique, and a subsequent analysis of GC samples using a quantitative method, a methyl-specific DNA microarray, revealed that merely 23% of GC samples showed RUNX3 P2 hypermethylation as compared to 46% with the conventional MSP technique [78]. Moreover, several more recent studies employing high-density DNA methylation microarrays of gastric, colorectal and breast cancer biopsies all gave the RUNX3 P2 methylation ratio a low ranking among the DNA hypermethylated genes [79][80][81][82][83][84].…”
Section: Runx3 Promoter Hypermethylation Is Not a Driver Of Gc Or Othmentioning
confidence: 92%